Does bowel preparation for inflammatory bowel disease surgery matter?. (5th September 2017) - Shwaartz, C.; Fields, A. C.; Sobrero, M.; Divino, C. M.
Abstract: Aim: The purpose of this study was to determine if bowel preparation influences outcomes in patients with inflammatory bowel disease undergoing surgery. Methods: The database of the American College of Surgeons National Surgical Quality Improvement Program, Procedure Targeted Colectomy, from 2012 to 2014 was analyzed. Inflammatory bowel disease patients undergoing colorectal resection with or without bowel preparation were included in the study. Results: In all, 3679 patients with inflammatory bowel disease were identified. 42.5% had no bowel preparation, 21.5% had mechanical bowel preparation only, 8.8% had oral antibiotic bowel preparation only and 27.2% had combined mechanical and oral antibiotic preparation. Combined mechanical and oral antibiotic preparation is associated with lower rates of anastomotic leak, ileus, surgical site infection, organ space infection, wound dehiscence and sepsis/septic shock. Conclusion: Combined mechanical and oral antibiotic preparation for inflammatory bowel disease patients undergoing colectomy is associated with decreased rates of surgical site infection, anastomotic leak, ileus. Combined bowel preparation should be the standard of care for inflammatory bowel disease patients undergoing colorectal resection.